Thermal Ramping Rate during Annealing of TiO2 Nanotubes Greatly Affects Performance of Photoanodes - Raza, Waseem; Hwang, Imgon; Denisov, Nikita; Schmuki, Patrik (physica status solidi (a), 2021)
Herein, highly ordered TiO2 nanotube (NT) arrays on a Ti substrate is synthesized in a fluoride-containing electrolyte, using the electrochemical anodization method, which yields amorphous oxide tubes. The effects of different thermal annealing profiles for the crystallization of the amorphous TiO2 NTs are studied. It is found that the temperature ramping rate has a significant impact on the magnitude of the resulting photocurrents (incident photon-to-current conversion efficiency [IPCE]) from the tubes. No appreciable changes are observed in the crystal structure and morphology of the TiO2 NTs for different annealing profiles (to a constant temperature of 450 °C). The electrochemical properties of the annealed TiO2 NTs are investigated using intensity-modulated photocurrent spectroscopy (IMPS), open-circuit potential decay, and Mott–Schottky analysis. The results clearly show that the annealing ramping rate of 1 °C s−1 leads to the highest IPCE performance. This beneficial effect can be ascribed to a most effective charge separation and electron transport (indicating the least amount of trapping states in the tubes). Therefore, the results suggest that controlling the annealing ramping rate is not only a key factor affecting the defect structure but also a powerful tool to tailor the physical properties, and photocurrent activity of TiO2 NTs.
CRIS-Team Scopus Importer:2021-05-07
Keywords: electrochemical anodization; photoanodes; photoelectrochemistry; ramping rates; TiO